Lack of relationship between Visna/maedi infection and scrapie resistance genetic markers - Salazar, Eider; Berriatua, Eduardo; Perez, Marta; Marín, Belen; Acín, Cristina; Martín-Burriel, Inmaculada; Reina, Ramsés; de Andrés, Damian; Amorena, Beatriz; Badiola, Juan José; Luján, Lluís (Spanish Journal of Agricultural Research, 2014)
The relationship between Visna/maedi virus (VMV) antibody status and scrapie genetic resistance of 10,611 Rasa Aragonesa sheep from 17 flocks in Aragón (Spain) was investigated. The fifteen most common PRNP gene haplotypes and genotypes were identified and the genotypes were classified into the corresponding scrapie risk groups (groups 1 to 5). ARQ (93.3%) and ARR (31.8%) were the most common haplotypes and ARQ/ARQ (56%) and ARR/ARQ (25.6%) were the most common genotypes. The frequencies of scrapie risk groups 1, 2, 3, 4 and 5 were 3.3%, 27.3%, 63.5%, 1.2% and 4.8%, respectively. Overall Visna/maedi seroprevalence was 53% and flock seroprevalence ranged between 21-86%. A random effects logistic regression model indicated that sheep VMV serological status (outcome variable) was not associated with any particular scrapie risk group. Instead, VMV seropositivity progressively increased with age, was significantly greater in females compared to males and varied between flocks. The absence of a relationship between VMV infection and scrapie genotypes is important for VMV control and specifically for sheep participating in an ELISA-based Visna/maedi control program.